Modulating membrane traffic regulators to impair breast cancer progression - Coito, Diana Catarina De Sousa (2020)
Breast cancer (BC) is the main cause of cancer-related mortality in women worldwide. Although this mortality has declined in recent years, approximately one third of BC patients die from metastasis. Therefore, to reduce morbidity and mortality by BC, it is crucial to develop therapies to impair metastasis. To accomplish this goal, we need a better understanding of the mechanisms that regulate the progression to a malignant and invasive state of the disease. Emerging evidence indicates that membrane traffic is subverted by cancer cells to promote tumor progression. Indeed, Arf-like (Arl) GTPases are key regulators of membrane traffic and their expression is modulated in several types of cancer, including BC. Arl proteins cycle between an active GTP-bound state and an inactive GDP-bound state. This interconversion is regulated by GTPase-activating proteins (GAPs), which inactivate Arls, and guanine nucleotide exchange factors (GEFs), which activate them. Interestingly, many cancers exhibit changes in the expression and/or activity of not only Arls but also their GAPs and GEFs. A member of this subfamily, Arl8, plays a crucial role in lysosome biology and has been shown to be involved in prostate cancer, making it an interesting player to study in BC progression. Moreover, given the importance of the activation switch for Arl function and the lack of knowledge about the role of Arl GAPs in BC, I also proposed to study ELMO-domain containing proteins (ELMOD1-3), a group of Arl GAPs, in BC progression. I found that ARL8 is upregulated in BC cell lines and patient-derived samples, is required for BC cell migration and is associated with worst survival rates in BC patients. I also showed that ELMOD1 and 2 are upregulated in BC cell lines and are required for BC cell migration. Therefore, these proteins could be targeted in an attempt to impair BC progression and metastasis.